The Illusion of Oversight: Fragmented Governance and Weak Legal Enforcement of Marine Environmental Degradation Caused by Nickel Mining Activities in North Kolaka - Petrus Sihombing; Iksan Saifudin (International Journal of Law, Social Science, and Humanities, 2026)
This study analyzes the phenomenon of institutional fragmentation and weak enforcement of marine environmental laws resulting from nickel mining activities in North Kolaka Regency. The research findings indicate that although Indonesia possesses a comprehensive regulatory framework for environmental protection, implementation at the local level has failed due to overlapping jurisdictions, weak inter-agency coordination, and the limited role of the regency government. These conditions give rise to the phenomenon of “the illusion of oversight”—a situation where formal oversight appears to be in place but is ineffective in preventing and addressing environmental violations. This study suggests a Multi-Stakeholder Approach-based Integrated Coordination Portal as a solution, integrating Early Warning System (EWS) and Whistleblowing System (WBS) technologies to enhance the responsiveness of oversight and transparency in environmental law enforcement. This model also emphasizes the importance of reconstructing district government authority through the delegation of environmental social control functions. These findings contribute to the development of a more integrated and enforcement-oriented environmental governance framework based on multi-level governance in developing countries.